Poly(butylene adipate-co-terephthalate) (PBAT)/AgFe2O4 biopolymer nanocomposite-based flexible triboelectric nanogenerator as a self-powered touch sensor - Vishnu Kadabahalli Thammannagowda; Kariyappa Gowda Guddenahalli Shivanna; Smitha Ankanahalli Shankaregowda; Stéphane Panier; Prashantha Kalappa (eXPRESS Polymer Letters)
Triboelectric nanogenerators (TENGs) offer a promising solution for self-powered sensor applications, but their viability depends on cost-effective and efficient designs. This study presents a simple, durable, low-cost, and biodegradable poly(butylene adipate-co-terephthalate)/AgFe2O4 (PBAT/AFO) based TENG, utilizing an innovative approach towards environmental sustainability. AgFe2O4 (AFO) nanoparticles, synthesized via combustion, were characterized using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. Synthesized AFO nanoparticles were then incorporated into PBAT to prepare polymer nanocomposite, with scanning electron microscopy (SEM) confirming their uniform dispersion. Electrical performance evaluations demonstrated efficient charge transfer, yielding a maximum output voltage of 49.15 V and a current of 4.9 μA under hand tapping. The PBAT/AFO-TENG successfully powered LEDs and an electronic calculator, showcasing its practical utility. Additionally, it functioned as a self-powered biomechanical sensor for human body motion detection, touch security, and touch counter for laboratory entry tracking. This work highlights the simplicity, environmental sustainability, cost-effectiveness, and versatility of PBAT/AFO-TENGs, positioning them as promising candidates for future portable electronics and sensing applications.